Culture, Identity, and Power. Issue 3 (May 2020) - Apple, Michael W.
In an earlier essay in the Reviewing Policy section of this journal, I documented the importance of the work of Stuart Hall in the development of critical theories in education, in our understanding of "race, " and in the development of much more nuanced analyses of cultural politics. I focused on two books: Familiar Stranger, Hall's personal memoir of political and cultural commitment; and Cultural Studies 1983, his lectures that provided the conceptual and political basis for a good deal of critical and nonreductive social and cultural analyses of the relationship between economic dynamics and structures and the rest of society. The two new books I discuss in the current essay provide us with a selection of many of the core reasons why he has been so influential in an entire range of critically oriented work in sociology, cultural studies, theories of race, "multiculturalism, " and identity, and increasingly in education.